2006
DOI: 10.1111/j.1747-5457.2006.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Migration, Faults and Overpressure, Part I: Calibrating Basin Modelling Using Petroleum in Traps - A Review

Abstract: the existence of oil or gas in both present-day and palaeo-accumulations of petroleum.Trapped petroleum represents an excellent source of information about hydrocarbon generation, expulsion, migration and accumulation, and the analysis of reservoired petroleum is a key tool in hydrocarbon exploration. Most geological information relates to the static rock framework, but oil which has moved through rock strata contains within it unique information for example on carrier interconnectivity and migration direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 68 publications
2
67
0
Order By: Relevance
“…The ratio of the tricyclic terpanes C 23 -C 29 (TRI) relative to the C 30 αβ-hopane increases during maturation, due to the greater generation rate of tricyclics compared to hopanes at elevated maturities or differences in thermal stabilities (Aquino Neto et al, 1982;Farrimond et al, 1998;Peters et al, 2005;van Graas, 1990). However, Karlsen et al (2004) and Karlsen and Skeie (2006) found that this ratio may be controlled by the GOR of the petroleum due to PVT changes during migration (cf. England and Mackenzie, 1989).…”
Section: Saturated Hydrocarbon Maturity Parametersmentioning
confidence: 93%
See 1 more Smart Citation
“…The ratio of the tricyclic terpanes C 23 -C 29 (TRI) relative to the C 30 αβ-hopane increases during maturation, due to the greater generation rate of tricyclics compared to hopanes at elevated maturities or differences in thermal stabilities (Aquino Neto et al, 1982;Farrimond et al, 1998;Peters et al, 2005;van Graas, 1990). However, Karlsen et al (2004) and Karlsen and Skeie (2006) found that this ratio may be controlled by the GOR of the petroleum due to PVT changes during migration (cf. England and Mackenzie, 1989).…”
Section: Saturated Hydrocarbon Maturity Parametersmentioning
confidence: 93%
“…Thus, any previously reservoired and lower maturity oil at this location appears to have been displaced by the later charge (cf. Gussow, 1954;Karlsen and Skeie, 2006;Sales, 1997). This interpretation implies ongoing lateral migration of hydrocarbons from the Tromsø Basin to the western part of the Hammerfest Basin (Fig.…”
Section: Variations In Maturation Parameters As Indications Of Mixingmentioning
confidence: 93%
“…Dahl and Speers, 1986;Karlsen et al, 1995;Leythaeuser and Rückheim, 1989;Tissot and Welte, 1984). A number of studies, devoted to understanding the reasons and consequences of diversities in petroleum composition, have already been undertaken long ago (Bailey et al, 1973a;Bailey et al, 1973b;Dahl and Speers, 1986;Espach and Fry, 1951;Evans et al, 1971;Hirschberg, 1988;Hunt, 1979;Justwan and Dahl, 2005;Karlsen et al, 1995;Karlsen and Skeie, 2006;Milner et al, 1977;Sage and Lacey, 1939;Tissot and Welte, 1984;Tyson, 1995). These studies have revealed that the factors that cause heterogeneities in petroleum composition in reservoirs can roughly be related to 1) variations in source rock organic facies and source rock maturity and 2) secondary alteration processes.…”
Section: 2mentioning
confidence: 99%
“…Therefore, oil and gas generally accumulate in the structurally highest part of the trap, provided that further movement is stopped by cap rocks. Still, most oil and gas will never reach the trap to form commercial accumulations but remains in the secondary migration pathways and petroleum will potentially also migrate to the surface as seeps or eventually become exhumed as in the case of Alberta Tar sands (England, 1994;Karlsen and Skeie, 2006). If buried deeper conversion of reservoired petroleum to graphite is likely.…”
mentioning
confidence: 99%
“…In addition, the hydrocarbon show thickness is positively correlated with the sandstone thickness, with a correlation coefficient (R 2 ) of 0.6701 (Figure 8b). Hydrocarbon migration and accumulation were significantly affected by the physical properties of the reservoir rocks, such as the porosity, permeability, sand ratio and sandstone thickness (Karlsen and Skeie, 2006). In general, the oil-bearing capacity of the reservoir rocks rises with increases in the porosity, permeability, sand ratio and sandstone thickness (Pang et al, 2013).…”
Section: Factors Controlling Hydrocarbon Distribution 51 Reservoir mentioning
confidence: 99%